Seci's Knowledge Management Based Training Model and Social Support for the Dental and Oral Health Maintenance Behavior of Children with Special Needs - Imam Sarwo Edi; Endang Purwaningsih Purwaningsih (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2023)
Introduction: Children with special needs are a high risk group for health problems, so they need help and cooperation with others to get and maintain health, including in maintaining their oral health. The condition of the oral cavity is strongly influenced by age factors (especially very young children), the severity of the disorder/abnormality, and environmental conditions where children are highly dependent on their parents, siblings, or caregivers in caring for their oral cavity. There needs to be a training model for parents and teachers. Methods: This research is analytic observational with a cross sectional approach to analyze the variation in magnitude or contribution between the variables studied based on the research objectives. The subjects studied were parents of children with special needs with a sample size of 110 people at SLB BC Optima and SLB Karya Bhakti Surabaya. Collecting data using a questionnaire, with the variables studied: Perception of the training model, social support, parental interest and dental and oral health maintenance behavior in children with special needs. Data analysis using Structural Equation Modeling (SEM) with Linear Structural Relationship (LISREL). Research results and analysis: The results show that: maintenance of oral health in children with special needs is influenced by training, social support and parental interest. The results of the model goodness test concluded that the final SEM model formed was a fit model, because of the 5 model goodness criteria, where the Chi-square value was 108.28 ( from the table value 138.81), RMSEA (0.054), GFI (0.936) , AGFI (0.905) and CFI (0.911) have met the fit model. Discussion: SECI Knowledge Management-Based Training Model and Social Support for Dental and Oral Health Maintenance Behavior for Children with Special Needs can be used as an alternative in an effort to improve dental and oral health maintenance behavior in children with special needs